Review of Grace Davie's Analytical Work in the Handbook of the Sociology of Religion and Its Relevance to the Indonesian Context - Roberto Arieza Martin Purba; Mohammad Taufiq Rahman; Yeni Huriyani (Sean Institute, 2026)
The contribution of Davie in